2008
DOI: 10.33585/cmy.60202
|View full text |Cite
|
Sign up to set email alerts
|

The wood-rotting bluing Psilocybe species in Central Europe - an identification key.

Abstract: The wood-rotting bluing Psilocybe species in Central Europe-an identification key.-Czech Mycol. 60(2): 173-192. An identification key to psychoactive bluing Psilocybe species growing on woody debris in Central Europe is presented. It is mainly based on microcharacters and includes 7 taxa (6 species and 1 variety) of the stirpes Serbica and Cyanescens (former "Psilocybe cyanescens complex"). Micro-, macroscopical, ecological and phenological characters and distribution of the taxa in Europe are presented and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…The recently described morphospecies P. bohemica, P. arcana, and P. moravica apparently represent just morphological and ecological varieties of P. serbica, and should accordingly be treated below species level. The species of the two groups can be unambiguously recognized microscopically by occurrence and shape of pleurocystidia (Borovička 2008). Psilocybe serbica now appears as a highly variable species characterized, e.g., by various robustness, shape and coloration of fruit-bodies, and microscopically by a large range of spore size and varying abundance/shape of pleuro-and cheilocystidia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The recently described morphospecies P. bohemica, P. arcana, and P. moravica apparently represent just morphological and ecological varieties of P. serbica, and should accordingly be treated below species level. The species of the two groups can be unambiguously recognized microscopically by occurrence and shape of pleurocystidia (Borovička 2008). Psilocybe serbica now appears as a highly variable species characterized, e.g., by various robustness, shape and coloration of fruit-bodies, and microscopically by a large range of spore size and varying abundance/shape of pleuro-and cheilocystidia.…”
Section: Resultsmentioning
confidence: 99%
“…This last species was described from North Africa as Hypholoma cyanescens Maire (1928), but no recent collections were available. All of the collections used for DNA extraction fit well with the morphological and ecological concept by Borovička (2008) (Table 1). When possible, holotype collections were used for sequencing (P. arcana, P. moravica, P. moravica var.…”
Section: Collections Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…arcana, and P. semilanceata are probably the only species containing sufficient for intoxication amounts of psilocin/ psilocybin that can grow in natural or near natural habitats in the Middle and North Europe. 60,[64][65][66] Psilocybe cubensis is the most popular natural source of psilocybin in the warmer regions of the Americas. In the United States, it can be found in the wild throughout the southeast to Texas and the Pacific Northwest.…”
Section: Psilocybin/psilocin As a Secondary Metabolitementioning
confidence: 99%
“…As has been recently demonstrated in the group of the European P. serbica M.M. Moser et E. Horak, the macro-and microcharacters can be highly variable in this species (Borovička 2008, Borovička et al 2011; therefore, one would not place emphasis on the macroscopic differences observed in the collections from Seattle and would attribute them to intraspecific variability of P. cyanescens.…”
Section: Introductionmentioning
confidence: 93%